Enabling real-time business intelligence 4th international workshop, BIRTE 2010, held at the 36th international conference on very large databases, VLDB 2010, Singapore, September 13, 2010, revised selected papers - Castellanos, Malu; Dayal, Umeshwar; Markl, Volker (Lecture notes in business information processing, 2011)
This book constitutes the thoroughly refereed conference proceedings of the 4th International Workshop on Business Intelligence for the Real-Time Enterprise, BIRTE 2010, held in Singapore, in September 2010, in conjunction with VLDB 2010, the International Conference on Very Large Data Bases. The volume contains six research papers, which are carefully reviewed and selected out of 12 submissions, plus the three keynotes presented at the workshop. The topics cover all stages of the business intelligence cycle, including capturing of real-time data, handling of temproal or uncertain data, performance issues, event management, and the optimization of complex ETL workflows.